Gonioinfradens paucidentatus (A. Milne Edwards, 1861) (Crustacea, Decapoda, Portunidae): a new alien crab in the Mediterranean Sea - CORSINI-FOKA, M.; PANCUCCI-PAPADOPOULOU, M.A.; KONDILATOS, G.; KALOGIROU, S. (Mediterranean Marine Science, 2010)
The first record for the Mediterranean Sea of the Red Sea/Indo-Pacific portunid Gonioinfradens paucidentatus (red swimming crab) is documented. A detailed description of the specimens collected at Rodos Island (southeastern Aegean Sea) is given, while possible introduction vectors of the species in the area are discussed.